Pregnant princess bride - Crews, Caitlin (Harlequin presents, 2024)
The billionaire has fought his attraction to her for years...until a baby scandal binds them together forever in this dramatic romance by USA TODAY bestselling author Caitlin Crews! It's one night only... until her royal pregnancy test! Attending Valentino Bonaparte's convenient wedding is torture for Princess Carliz. Years ago, she shared an incandescent kiss with the brooding Italian--she's craved more ever since. When the ceremony is called off, they finally get the chance to surrender to their wildest temptations. But in the morning, Valentino still walks away... Three months after their passionate night wrecked her forever, Carliz must tell Valentino he left her with more than a broken heart--she's expecting his baby! And he's determined his heir will not be illegitimate...